2021
DOI: 10.1038/s41398-021-01633-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural contributors to trauma resilience: a review of longitudinal neuroimaging studies

Abstract: Resilience in the face of major life stressors is changeable over time and with experience. Accordingly, differing sets of neurobiological factors may contribute to an adaptive stress response before, during, and after the stressor. Longitudinal studies are therefore particularly effective in answering questions about the determinants of resilience. Here we provide an overview of the rapidly-growing body of longitudinal neuroimaging research on stress resilience. Despite lingering gaps and limitations, these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 125 publications
0
39
0
1
Order By: Relevance
“…Importantly, there is evidence that rIFG activation and connectivity with other fear-related brain regions can improve with trauma-focused treatment (Rousseau et al, 2019 ) and may improve emotion and fear regulation when targeted using transcranial direct current stimulation (tDCS) (Herrmann, Beier, Simons, & Polak, 2016 ), although findings are mixed (Smits, Geuze, Schutter, van Honk, & Gladwin, 2021 ). A recent resilience model of PTSD has been suggested whereby post-trauma biomarkers of cognitive control, specifically dorsolateral PFC structural integrity, promotes resilience (Roeckner, Oliver, Lebois, van Rooij, & Stevens, 2021 ). Our findings suggest that the rIFG may be another cognitive control region likely implicated in resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is evidence that rIFG activation and connectivity with other fear-related brain regions can improve with trauma-focused treatment (Rousseau et al, 2019 ) and may improve emotion and fear regulation when targeted using transcranial direct current stimulation (tDCS) (Herrmann, Beier, Simons, & Polak, 2016 ), although findings are mixed (Smits, Geuze, Schutter, van Honk, & Gladwin, 2021 ). A recent resilience model of PTSD has been suggested whereby post-trauma biomarkers of cognitive control, specifically dorsolateral PFC structural integrity, promotes resilience (Roeckner, Oliver, Lebois, van Rooij, & Stevens, 2021 ). Our findings suggest that the rIFG may be another cognitive control region likely implicated in resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Although different resilience assessment questionnaires have been used in different studies, overall results support the idea that low resilience may be a non-specific vulnerability factor in different psychiatric disorders, including depression, following exposure to severe stressors, such as the ongoing pandemic. However, resilience is currently conceptualized as a complex and dynamic quality, including multiple resilience factors that range from neurobiological and psychological features of the individual to the social context and relationship networks ( Ayed et al, 2019 ; Kageyama et al, 2021 ; Kalisch et al, 2019 ; Perna et al, 2020 ; Roeckner et al, 2021 ). In line with this, we also found that preceding low levels of support by relatives or household members in difficult situations was as an additional significant predictor of first-onset PMDD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, converging evidence from these studies suggest hyperactive amygdala as a predisposing factor for PTSD [4][5][6] . However, these studies have largely used task-based fMRI that is tailored to investigate targeted neural regions of interest, and thus generally leave open the question regarding the involvement of larger scale neural networks, beyond the regional focus 5 .…”
Section: Introductionmentioning
confidence: 98%
“…These studies have identified a number of critical brain regions that may be involved in resilience but could also potentially reflect the symptoms that have already arisen 4 . A smaller number of studies, with generally limited sample sizes, has assessed which brain response prospectively predict later trauma symptom development by taking advantage of longitudinal designs with fMRI scans acquired before trauma exposure 5 . Interestingly, converging evidence from these studies suggest hyperactive amygdala as a predisposing factor for PTSD [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation